THE ROLE OF LAND DEED OFFICIAL REGARDING LEGAL CERTAINTY OF COMPLETE SYSTEMATIC LAND REGISTRATION - Yubaidi, Ricco Survival (Jurnal Hukum dan Peradilan, 2020)
As an acceleration program for land registration in Indonesia that is directly led by the President, Complete Systematic Land Registration (PTSL) should provide a guarantee of legal certainty and protection regarding land ownership rights. However, in fact, the role of the land deed official (PPAT), as a public official who receives a mandate from the Governmental Regulation no. 24 of 1997 regarding Land Registration, is not found within the implementation of PTSL. The present research aimed to investigate the role of PPAT in the implementation of PTSL. Using normative legal approach, this study employed literature study to collect the primary data. This research found that PPAT does not have any role in regulatory legislation regarding PTSL. If we see Governmental Regulation no. 24 of 1997, all transfers occurring after the issuance of the regulation requires PPAT’s deed as written evidence of land ownership. The adjudication committee as the PTSL implementer supposes to collaborate with PPAT to make sure that PTSL meets the steps of juridical data collection in order to obtain an orderly, complete land registration that provides legal certainty regarding land ownership right.